Federalizacja Unii Europejskiej. Analiza i ocena zjawiska w kontekście pojęcia rodziny i małżeństwa. - Świątkowski, Waldemar (Civitas et Lex, 2022)
In recent years, in the European Union, constantly stronger tendencies have been observed that refer to the actual extension of European Union institutions’ competencies to those areas of life that were not imposed to them by the decisions of member states in the treaties. This is how the process of federalization is supposed to look like – to aim at creating within the EU one ‘cosmopolitan empire’ in the place of current union of nations. The aim of the article is the attempt to reveal the characteristics of the spirit exposed by the European’s institutions of federative law and order, prove if it was really included in European documents and explain from which law philosophy it derives from, what it can mean – in the case of its institutional complementation – for the understanding of traditional family and marriage pattern as well as pluralistic forms of life. In the article, I would also like to confront cosmopolitan federation’s idea with the spirit of classical and Christian philosophy spirit as well as answer, among other things, to the following question: is the spirit able to face the multicultural and multinational European complexity, or is it rather the next historical attempt of ideological possession of nations, culture and axiology?